Dermatosparaxis in two Limousin calves. Issue 1 (December 2016) - Carty, Catherine; Lee, Alison; Wienandt, Nathan; Stevens, Edward; Alves, Derron; Browne, John; Bryan, Jill; Ryan, Eoin; Cassidy, Joseph
Abstract Background An unusual presentation of skin disease was identified in two related neonatal Pedigree Limousin calves presented to University Veterinary Hospital, University College Dublin, following detailed post mortem examination a diagnosis of dermatosparaxis was made. Dermatosparaxis in animals or Ehlers Danlos Syndrome, which is the analogous condition seen in humans, is a connective tissue disorder characterised by extreme skin fragility. To the authors' knowledge this is the first report of such a diagnosis in the Limousin breed and the features of this lethal phenotype were severe in comparison to previous reports of the condition. Case presentation Two calves, which were full siblings, a pedigree Limousin bull (Calf A) and pedigree Limousin heifer (Calf B) were examined clinically after presenting collapsed since birth, both had grossly abnormal skin with multiple skin fissures visible and both calves were subsequently euthanised. Both calves underwent gross post mortem examination, after which histological samples were reviewed and electron microscopical examination of selected skin samples was carried out. Histological features of dysplastic dermal collagen were identified. The diagnosis of dermatosparaxis in the Limousin breed was confirmed. Genetic testing was conducted to determine if the current cases had the same mutation as has previously been described in Belgian Blue cattle. Some common parentage was traced but genetic testing did not show a similar mutation to that previously described in cattle. The specific genetic cause in this case is unknown. Conclusions This is the first report of dermatosparaxis in the Limousin and the presentation of the dermatosparaxis phenotype has some noteworthy features thus further genetic testing is required to pinpoint the causative mutation or other genetic defect. Given the popularity of the breed and the lethal nature of the phenotype in this case it is important to raise awareness of the condition.